Har leksikografien bruk for omgrepet ’motivasjon’? - Myking, Johan (Nordiske Studier i Leksikografi, 2010)
The contribution deals with the topic of lexical motivation and its usefulness for lexicography. Motivation is often interpreted as a synonym for transparency or compositionality, one consequence being that motivated lexemes should not be lemmatised. Current terminology seems to put more emphasis on motivation than does lexicography. In terminology the concept has normative as well as semasiological aspects and motivation has been stretched beyond the traditional saussurean concept of ‘relative’ motivation, i.e. derivation and composition. Recent cognitive terminology emhasises metaphor, and cognitive definitions of motivation include language-internal as well as language-external factors. It is argued that the discussion on motivation found in terminology is relevant to lexicology. If, however, lexicography is delimited from lexicology in a way that lemmatisation becomes the only important issue relevant to motivation, the question of usefulness cannot unambigously be given an affirmative answer.